Coupled acoustoplasmonic resonators: the role of geometrical symmetries - Castillo López de Larrinzar Beatriz; García Jorge M.; Xiang Chushuang; Lanzillotti-Kimura Norberto D.; García-Martín Antonio (Nanophotonics)
Acoustoplasmonic resonators, such as nanobars and crosses, are efficient acousto-optical transducers. The excitation of mechanical modes in these structures strongly depends on the spatial profile of the eigenmodes of the resonator. Using a system of two identical gold elongated bars placed on a silicon dioxide substrate, we examine how breaking mirror symmetries affects the optical and acoustic properties to provide insights in the design of acoustoplasmonic metasurfaces for nonsymmetric acousto-optical transducers. Our findings show that the absence of mirror symmetries affects differently the optical and nanomechanical response. Broken mirror symmetries not only couple nanomechanical modes existing in single bars but introduce new torsional resonant modes.